PENGEMBANGAN INSTRUMEN INTEGRATED SCIENCE TEST TIPE PILIHAN GANDA BERALASAN UNTUK MENGUKUR HOTS PESERTA DIDIK - Yeni Widiyawati; Indri Nurwahidah; Dwi Septiana Sari (FKIP Universitas Jember, 2019)
HOTs is the main purpose of 21st-century science learning. Individu with HOTs will able to make a connection between facts and concepts, apply it into any new situation to solve the problem. The aim of this research was to developed integrated science test instrument to measure HOTs level of junior high school students. Oriondo and Antonio models’ was adapted and used in this research method. The test was developed in the reasoning-multiple choice form with three category based on PISA and Marzano HOTs competencies. The item analysis involved content validity, empirical validity, reliability, and difficulty index. Rasch model analysis through Quest and Ministep software output showed (1) Mean of INFIT MNSQ level at 1.00±0.12 that shows fit item with Rasch Model or empirical validity of items; (2) Level of INFIT MNSQ for all item between 0.77 and 1.33; (3) Vary of difficulty index; 34 items were at difficulty index level between -2 and +2; (4) junior high school students’ HOTs in SMP IT Multazzam Banyumanik was at low level because they are difficult in giving explanations or arguments about the options that have been selected. Thus, the integrated science test instrument developed can be used to measure students' HOTs.